PERBUATAN MEMBERIKAN GANJA KEPADA ORANG LAIN SEBAGAI ALTERNATIF PENGOBATAN DITINJAU DARI SIFAT MELAWAN HUKUM DALAM HUKUM PIDANA (STUDI KASUS FIDELIS ARIE SUDEWARTO) - Maria Tarigan; Nathalina Naibaho (Riau Law Journal, 2020)
The use of marijuana in medication has been criminalized in Indonesia since 1997. Twenty years after, Fidelis Arie Sudewarto violated the rule by administering marijuana as an alternative means of medication for his spouse, Yeni Riawati. Various public opinions emerged, indicating a shift of paradigm on the use of marijuana for medication, and this affects the fulfillment of "unlawful nature" which is expressly stated as one of the elements in the formulation of offense as stipulated in Article 116 paragraph (2) Law Number 35 of 2009, especially in assessing the material unlawfulness nature (materieele wederrechtelijkheid) of the act. This study discusses the case of Fidelis from the perspective of criminal law, namely how the fulfillment of the element of unlawful nature and whether there is a basis which then abolish the unlawful nature in the acts committed by Fidelis Arie Sudewarto.